1996
DOI: 10.1029/95ja03063
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of transient events in the outer dayside magnetosphere

Abstract: The AMPTE CCE satellite frequently observed transient (1 < r < 8 min) events marked by magnetic field strength increases and bipolar magnetic field signatures (peak-topeak amplitudes > 4 nT) while in the outer dayside magnetosphere. We report a survey of 59 prominant events observed from August to November 1984. The bipolar signatures and minimum variance analysis reveal that most events move poleward and antisunward, except in the immediate vicinity of local noon. Here the motion of the events appears to be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 47 publications
(52 reference statements)
2
48
3
Order By: Relevance
“…In the context of this debate, Kawano et al (1992) introduced a "characteristic time" (t char , defined as the time between the positive and negative peaks in the B N signature) to distinguish between longer events with bipolar B N signatures (t char >90 s) which were found to occur over a wide range of McIlwain L-shells and were not correlated to periods of reconnection as evidenced by AE index or southward interplanetary magnetic field (IMF), and shorter events (t char <90 s) which occurred nearer the magnetopause during periods of high AE index and southward IMF. Sanny et al (1996) investigated similar signatures, over a wider range of radial distances from Earth and also concluded that the shorter events were FTEs, whilst the longer events were more likely to be due to magnetopause waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of this debate, Kawano et al (1992) introduced a "characteristic time" (t char , defined as the time between the positive and negative peaks in the B N signature) to distinguish between longer events with bipolar B N signatures (t char >90 s) which were found to occur over a wide range of McIlwain L-shells and were not correlated to periods of reconnection as evidenced by AE index or southward interplanetary magnetic field (IMF), and shorter events (t char <90 s) which occurred nearer the magnetopause during periods of high AE index and southward IMF. Sanny et al (1996) investigated similar signatures, over a wider range of radial distances from Earth and also concluded that the shorter events were FTEs, whilst the longer events were more likely to be due to magnetopause waves.…”
Section: Introductionmentioning
confidence: 99%
“…Sibeck et al, 1989;Lanzerotti, 1989;Sibeck, 1990;Elphic, 1990;Sckopke, 1991;Lockwood, 1991;Sibeck, 1992;Smith and Owen, 1992;Kawano et al, 1992;Elphic et al, 1994;Song et al, 1994Song et al, , 1996Newell, 1995, 1996;Sanny et al, 1996). In the context of this debate, Kawano et al (1992) introduced a "characteristic time" (t char , defined as the time between the positive and negative peaks in the B N signature) to distinguish between longer events with bipolar B N signatures (t char >90 s) which were found to occur over a wide range of McIlwain L-shells and were not correlated to periods of reconnection as evidenced by AE index or southward interplanetary magnetic field (IMF), and shorter events (t char <90 s) which occurred nearer the magnetopause during periods of high AE index and southward IMF.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been the cause of much debate (e.g. Lanzerotti, 1989;Elphic, 1990;Lockwood, 1991;Smith and Owen, 1992;Kawano et al, 1992;Elphic et al, 1994;Song et al, 1994Song et al, , 1996Newell, 1995, 1996;Sanny et al, 1996). In particular, Kawano et al (1992) studied bipolar signature events near the low-latitude magnetopause, and concluded that long (B N peak-to-peak time-scale >90 s) events showed no correlation with the interplanetary magnetic field (IMF) or AE index and occurred over a wide range of McIlwain L-shells.…”
Section: Introductionmentioning
confidence: 99%
“…However short (time-scale <90 s) events tended to be observed near the magnetopause during periods of southward IMF and high AE index, and were ascribed to reconnection. Sanny et al (1996) used similar criteria to identify bipolar "transient events" observed by the AMPTE CCE satellite across a wider range of radial distances from the Earth. The occurrence of these transient events was not correlated with the IMF orientation, and they were interpreted as signatures of solar wind/foreshock pressure pulses.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sibeck et al (2003) showed that for a spiral IMF the postnoon first impact created activity that propagated past noon toward dawn. Sanny et al (1996) studied dayside magnetospheric responses to observed increases in the IMF strength and bi-polar fluctuations in B X exceeding 4 nT. They argue that pressure pulses are the dominant cause of events observed in the closed field line part of the outer magnetosphere.…”
mentioning
confidence: 99%